A história da ludicidade no desenvolvimento das crianças da educação infantil - FARIAS, Janaína Rodrigues (2022)
The research presented here has as its main objective to analyze the importance of using play in the teaching-learning process in early childhood education. The research is based on the following issue: how are recreational activities worked through games and games and how can the act of playing offer learning resources to early childhood education students? Methodologically, the research is bibliographical in nature, which focuses on theoretical deepening on the topic addressed, based on materials already developed, such as books, scientific articles, and has the support of theorists, such as: Kishimoto (1993; 2011) , Vygotsky (1984; 2007), Sônia Kramer (1988; 2012), among others. The results show that games and games, when used in the learning of children in kindergarten, can be a great knowledge tool for the student in subjects studied in the classroom, also helping the student's growth in the affective, creative, social conception and cultural. The research carried out showed that it is through play that children communicate with the world around them, learning to live in society, understanding rules, reciprocal relationships, establishing limits and their socialization dynamics.